Człowiek i prawda w aspekcie nauk przyrodniczych - Andrzej Abdank-Kozubski (Studia Ecologiae et Bioethicae, 2003)
Human plays a crucial role in the creation of science and the process of its development. The accepted idea of science determines, in turn, the position of humans in nature. Both modernity and contemporaneity suggest certain general concepts of science, as well as substantially and specifically influence the vision of mutual relations between humans and nature. The simple relationship between science and truth, which stemmed from positivism and which justified any form of the exploitation of nature, has been seriously questioned in the new idea of science. Consequently, the scheme, in which nature was treated as an object of unlimited use disappeared. Approaching the truth became a process showing various relationships and connections between humans and nature. Being still a subject in relation to nature, humans appeared one of its definitely determined components.